Chronic Neck Swelling: A Case Report of Migrating Fish Bone - Saiful Islam; Mawaddah A; Wong, Timothy Leong Wei (King's College Circle, University of Toronto, 2024)
Background: Foreign bodies in the upper aerodigestive tract are frequently seen in otolaryngological practice, but migration of foreign body and oesophageal penetration are rare occurrences. Most reported cases of migration in literature involve fish bones, which are usually found in the lateral neck soft tissue or thyroid lobule. This can cause serious complications if left untreated. In most cases, fish bones can be removed safely by endoscopy, but they may migrate extraluminally to the skin in rare cases. Computed tomography (CT) neck with contrast is the investigation of choice to confirm migration. Case presentation: We present a case of an elderly lady with fish bone ingestion which migrated and embedded itself over the right thyroid cartilage region that required open surgery for removal. In this case, the patient underwent two open surgeries to locate the presence of the foreign body despite the CT neck done to aid in mapping intraoperatively. We used surgical clips in the first unsuccessful operation in locating the foreign body, and later performed a repeat CT scan and the clips were used to pinpoint the exact location of the foreign body during second surgery. By doing so, we successfully managed to remove the foreign body and patient was discharged well. Conclusion: This case has illustrated how versatile surgical clips are in helping us to locate the position of the foreign body rather than blindly exploring and causing further iatrogenic injury. With supplementation from a thorough repeat CT scan, we do think that in a presenting case of foreign body migration with difficulty locating the exact foreign body location, imaging adjunct such as C arm fluoroscopy and ultrasound guidance as reported in the literature can be used to avoid unnecessary iatrogenic injury and cause more harm to the patient.